2018
DOI: 10.1111/jbi.13214
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA tracks the mainland extinction and island survival of the Tasmanian devil

Abstract: Aim The Tasmanian devil (Sarcophilus harrisii), currently restricted to the island of Tasmania, was found over most of the Australian mainland prior to its extinction ~3,000 years ago. Recent debate has focused on the roles of humans, climate change and dingoes as drivers of the mainland extinction. Determining past genetic diversity and population dynamics of both populations is a fundamental component to understand why the species went extinct on mainland Australia, but survived in Tasmania. Here, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 95 publications
(170 reference statements)
0
30
0
Order By: Relevance
“…Habitat area is a key determinant for population sustenance (Gibbs, ; Lino, Fonseca, Rojas, Fischer, & Ramos Pereira, ) and maintaining viable (i.e., genetically diverse, noninbred) populations (Frankham, , ). Multiple studies have shown that island species have less genetic diversity and increased inbreeding compared to their mainland counterparts (Brüniche‐Olsen, Jones, et al, ; Eldridge et al, ; Frankham, ; Palkopoulou et al, ). We add to this body of evidence by exploring how genomic diversity is influenced by the size of the island itself.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat area is a key determinant for population sustenance (Gibbs, ; Lino, Fonseca, Rojas, Fischer, & Ramos Pereira, ) and maintaining viable (i.e., genetically diverse, noninbred) populations (Frankham, , ). Multiple studies have shown that island species have less genetic diversity and increased inbreeding compared to their mainland counterparts (Brüniche‐Olsen, Jones, et al, ; Eldridge et al, ; Frankham, ; Palkopoulou et al, ). We add to this body of evidence by exploring how genomic diversity is influenced by the size of the island itself.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been implicated in the mainland extinction of the devil and the thylacine. These include climate, humans and dingoes, although recent modelling suggests that the influence of dingoes was not strong [89,90]. Dingoes never reached Tasmania and the thylacine was hunted to extinction there in the twentieth century, leaving the devil as the largest predator [91].…”
Section: Case 3: Top Predators In Australiamentioning
confidence: 99%
“…by relaxing lethal control of apex predators; Cunningham et al 2019b). In areas of the Australian mainland where restoring dingo populations remains socially unacceptable, it is worth exploring whether devils could fill the void, given they were present on the mainland until approximately 3200 years ago (White et al 2018) and the synergistic causes of their extinction (climate, dingoes and human intensification) are sufficiently understood (Brown 2006;Br€ uniche-Olsen et al 2014;Prowse et al 2014;Br€ uniche-Olsen et al 2018). This could begin with a carefully controlled experimental reintroduction of devils to a bounded landscape to assess whether they can perform key top-down functions in ecosystems on mainland Australia, as modelling suggests (Hunter et al 2015).…”
Section: Discussionmentioning
confidence: 99%